The Effectiveness of Forming a Pancasila Student Profile by Implementing a Project Based Learning Model on Newton's Law Material - Tri Maria Wea; Putut Marwoto; Ellianawati Ellianawati (Universitas Negeri Semarang, 2023)
This study aims to find the effectiveness of forming a Pancasila student profile by applying a project based learning model in the physics learning process for Newton's Law material in class X MIPA students at SMAN 1 Bajawa. The dimensions of the Pancasila Student Profile include three dimensions, namely the ability to think critically, creatively, and mutual cooperation. This type of research is a mixed method sequential explanatory. Data collection instrument were tests and observation guidelines. The results of the data analysis show that the project based learning model contains Pancasila student profile values. Based on the research data, it was obtained that the studentsâ€™ abilities on the Pancasila student profile is in the good category. The ability to critical thinking and crietive thinking has increased and can foster an attitude of mutual cooperation in students after being treated using a project based learning model. The N-gain value of critical thinking is 64.3% and classic completeness is 93%, the N-gain creative thinking increases by 68.5% and classic completeness is 90%, the students' cooperative attitude is 83% in the good category. This shows that the project based learning model that was implemented is effective in strengthening the profile of Pancasila students.Â The class control uses theÂ PBL model N-gain value of critical thinking was 57.7%, the N-gain creative thinking increased by 53.3%, the mutual cooperation attitude of the students was in the with the medium category.